Optimal parametrisation of the Pariser-Parr-Pople Model for benzene and biphenyl - Bursill, R; Castleton, C; Barford, W (1998)
We obtain a parametrisation of the Pariser-Parr-Pople model of the π-conjugated systems which is optimal for benzene, biphenyl and poly(para-phenylene). We first optimise agreement with experiment for a number of low-lying excitations of benzene, leading to a phenyl transfer integral of 2.539 eV, an on-site Coulomb energy of 10.06 eV and a relative error of 2.8%, compared with 7.4% using the standard values. We next optimise agreement for the long axis polarised optical transitions of biphenyl with absorption data, leading to a bridging bond transfer integral of 2.22 eV.